2014
DOI: 10.1155/2014/310194
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Childhood Pulmonary Tuberculosis by Xpert MTB/RIF Assay Using Bronchoalveolar Lavage Fluid

Abstract: In order to evaluate the diagnostic accuracy of the Xpert MTB/RIF assay on childhood pulmonary tuberculosis (PTB) using bronchoalveolar lavage fluid (BALF), we evaluated the sensitivity, specificity, positive predictive value, and negative predictive value of Xpert MTB/RIF assay using BALF in comparison with acid-fast bacilli (AFB) microscopy and Mycobacterium tuberculosis (MTB) culture for diagnosing childhood PTB using Chinese “composite clinical reference standard” (CCRS) as reference standard. Two hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…In a comparative study performed by QQ Yin et al in 250 Chinese children of suspected TB showed Sensitivity of AFB microscopy, MTB culture, and GeneXpert MTB/RIF assay was 8.4%, 28.9%, and 53.0%, respectively. GeneXpert MTB/RIF assay could detect 33.9% of cases with negative MTB culture, and 48.7% of cases with negative AFB microscopy [18]. In a prospective study on children by Brown et al showed culture of gastric lavage had sensitivity only 30% and induced sputum 39% [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study performed by QQ Yin et al in 250 Chinese children of suspected TB showed Sensitivity of AFB microscopy, MTB culture, and GeneXpert MTB/RIF assay was 8.4%, 28.9%, and 53.0%, respectively. GeneXpert MTB/RIF assay could detect 33.9% of cases with negative MTB culture, and 48.7% of cases with negative AFB microscopy [18]. In a prospective study on children by Brown et al showed culture of gastric lavage had sensitivity only 30% and induced sputum 39% [6].…”
Section: Discussionmentioning
confidence: 99%
“…[50] has concluded that this test will not be a crucial diagnostic tool in high burden countries, the WHO endorsed its use in children in 2013. Several studies published on its use in the pediatric population have shown promising results be it in gastric lavage [51,52], sputum [53][54][55][56][57][58][59], bronchoalveolar lavage specimens [60], or stool in HIV-infected patients [61].…”
Section: Xpert Mtb/rifmentioning
confidence: 99%
“…Nineteen studies are available on the use of Xpert MTB/RIF in the pediatric population [64,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Overall, the sensitivity of this test in respiratory samples compared to culture for TB detection ranged between 39 and 100%, and in particular for sputum varied from 57 to 100%, for gastric lavage/aspiration from 64 to 80% and for nasopharyngeal aspirate from 39 to 65%.…”
Section: Xpert Mtb/rifmentioning
confidence: 99%
“…Overall, the sensitivity of this test in respiratory samples compared to culture for TB detection ranged between 39 and 100%, and in particular for sputum varied from 57 to 100%, for gastric lavage/aspiration from 64 to 80% and for nasopharyngeal aspirate from 39 to 65%. Specificity, for all respiratory specimens varied from 70 to 100% [64,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] (TABLE 3). A recent meta-analysis proved that Xpert MTB/RIF provides an excellent sensitivity in smear positive children for both gastric lavage/aspirate and expectorated/induced sputum (95%, 95% CI: 83-99 and 96%, 95% CI: 90-99, respectively) and an acceptable sensitivity for both sample types in smear-negative culture-positive children (62%, 95% CI: 44-80 and 55%, 95% CI: 41-69, respectively) [68].…”
Section: Xpert Mtb/rifmentioning
confidence: 99%
See 1 more Smart Citation